Bottleneck and gene flow effects impact the genetic structure of seed-propagated apricot populations in Moroccan oasis agroecosystems. Issue 2 (4th December 2013) - Mamouni, Ali; El Bakkali, Ahmed; Lambert, Patrick; Krichen, Lamia; Oukabli, Ahmed; Audergon, Jean Marc; Chatelet, Philippe; El Modafar, Cherkaoui; Khadari, Bouchaib
Abstract : In order to highlight the genetic status and origin of Moroccan apricot populations, trees were collected from ten oasis agroecosystems and analysed with AFLP markers. A total of 87 accessions and 12 cultivars grown in Moroccan orchards, including 'Canino' and 'Del Patriarca' cultivars, were surveyed and compared with in situ Tunisian and ex situ Montfavet (France) collections. Our results highlighted a narrow genetic diversity in the Maghreb region (Tunisia and Morocco) associated with a strong differentiation from the other groups, which supports a bottleneck effect. A similar model was illustrated at a finer geographical scale, i.e. the Draa Valley in Morocco. Genetic structure appeared as two major clusters subdivided into six sub-clusters in which Moroccan germplasm constituted specific groups in comparison with other Mediterranean apricots. Moroccan germplasm was classified into three sub-clusters, two of which were formed by genotypes related to 'Del Patriarca' and 'Canino', respectively. The present study highlights the wide Moroccan apricot's diversity in traditional agroecosystems, and also suggests a substantial gene flow occurring from recently introduced cultivars ('Canino' and 'Del Patriarca') to local apricot populations, thus leading to local germplasm diversification through seedling propagation. If we consider its geographical position, the historical diffusion of the species and farming practices, Morocco could be viewed as an additional centre of secondary diversification for apricot. Understanding the origin and specificity of local apricot populations is crucial for managing local collections in regard to adaptive traits for arid and Saharan conditions as well as for introducing local genetic resources into current breeding programmes.